'Good' Governance Principles in Spatial Planning at Local Scale. (2016) - Virtudes, Ana
Abstract: The development of countries, the economy of cities and how cities should be governed is a subject that has been studied by several organizations, in many countries, concerning different levels of public administration. Some of these studies have their focus on fields such as sustainability and environment, sensorial networks or spatial planning. Therefore, this research in based on a literature review and it is focused on the significance of governance role at local scale, for the final decisions that will address the different spatial planning policies and city shapes as a competitive physical form, according to the strengths and weaknesses of a competitive process. It will analyses the good governance principles related on spatial planning actions, considering that Governmental and non-governmental organizations utilize knowledge to reinforce their own position of power, as one of the ways of improving competitiveness, helping to achieve more efficient level of governance, exploring the technology. It will conclude about the needs to identify processes used by local governance to facilitate the involvement of local community in spatial planning decision making, concerning their city or neighborhood.